Promoting Innovation, Creativity and Entrepreneurship Skills in Science Education Students: A Panacea for Employability - Chinyere, Agommuoh P; C, Ndirika M (Journal of Education and Practice, 2020)
Purpose: The purpose of this study is to investigate how science teachers can teach science education students in order to promote innovative, creative and entrepreneurship skills in them to enable them become employable in the labour market. Unemployment in Nigeria is a time bomb waiting to explode at any time except proper and effective interventions is put in place to mitigate the impact of high youth unemployment. This paper uses descriptive survey research design. The population of the study is all the 933 science education students in the Department of Science Education of Michael Okpara University of Agriculture, Umudike. Methodology: A simple random sampling technique was used to sample 100 (80 males and 70 females) science education students. Three research questions and three hypotheses that were tested at 0.05 level of significance guided the study. The instrument for data collection was the researcher's developed questionnaire of the four-point Likert Scale type of Strongly Agree (SA), Agree(A), Disagree(D) and Strongly Disagree (SD) which are rated 4, 3, 2 and 1 respectively. The instrument was validated and its coefficient of reliability obtained as 0.89. Data collected were analyzed using mean to answer the research questions and t- test to analyze the hypotheses. Findings: The results obtained indicated that teaching science students in such a way that they will be able to make use of facilitation technique that allows for sharing ideas and freedom to innovate; develop skills for accessing funds and accounting; develop critical skills that will enhance innovative ideas; develop collaborative skills needed for joining cooperative societies like producer and consumer cooperative and develop the ability to organize and build network are some of the things the science teacher should do to promote innovation, creativity and entrepreneurship skills in science students. Unique Contribution to theory, practice and policy: Based on the findings, it was therefore recommended that science education students should be taught science properly so that they can develop critical skills to enhance their innovative ideas. Also, science students should be taught science in a way that will help them develop collaborative skills needed for joining and organizing cooperative societies.